The Synergistic Inhibition of Coronavirus Replication and Induced Cytokine Production by Ciclesonide and the Tylophorine-Based Compound Dbq33b - Yue-Zhi Lee; Hsing-Yu Hsu; Cheng-Wei Yang; Yi-Ling Lin; Sui-Yuan Chang; Ruey-Bing Yang; Jian-Jong Liang; Tai-Ling Chao; Chun-Che Liao; Han-Chieh Kao; Jang-Yang Chang; Huey-Kang Sytwu; et al. (MDPI AG, 2022)
Ciclesonide is an inhaled corticosteroid used to treat asthma and has been repurposed as a treatment for mildly ill COVID-19 patients, but its precise mechanism of action is unclear. Herein, we report that ciclesonide blocks the coronavirus-induced production of the cytokines IL-6, IL-8, and MCP-1 by increasing IκBα protein levels and significantly decreasing p65 nuclear translocation. Furthermore, we found that the combination of ciclesonide and dbq33b, a potent tylophorine-based coronavirus inhibitor that affects coronavirus-induced NF-κB activation a little, additively and synergistically decreased coronavirus-induced IL-6, IL-8, and MCP-1 cytokine levels, and synergistically inhibited the replication of both HCoV-OC43 and SARS-CoV-2. Collectively, the combination of ciclesonide and dbq33b merits consideration as a treatment for COVID-19 patients who may otherwise be overwhelmed by high viral loads and an NF-κB-mediated cytokine storm.